Optimization of Access Point Positioning on Wi-Fi Networks Using the K-Means Clustering Method - Faiz Ainun Karima; Ary Mazharuddin Shiddiqi (IPTEK The Journal for Technology and Science, 2022)
Uneven distribution is a common problem in setting up access points where some areas have many signals colliding with each other and others have no signals at all (blank spots). As a result, proper access point positioning on the WI-FI network is required to optimize the number of access points used and the signal strength received while maintaining the same coverage area's functionality. In this study, signal strength measurement is used to obtain the estimated distance using the Received Signal Strength Indicator (RSSI) method. The server analyzes using the K-Means Clustering algorithm to cluster the observation area. The output of this classification is the mapping of dense regions (traffic) and loose regions to determine the coverage areas of each access point. This approach aims to optimize the placement of access points in terms of their number and specifications.